Ethnic Minorities in Lithuania and Latvia: Between Political Category and Ethnicity - Valevičius, Vytautas; Kraniauskas, Liutauras (Sociologija. Mintis ir veiksmas, 2001)
Representation politics of ethnic minorities in Lithuania and Latvia subsumes different minor ethnic groups under one category of minorities’ ethnicity. This model of common identity is shaped by juridical and political discourses representing an out-group definition. Differences in everyday cultural practices and social distance among ethnic groups set ethnic boundaries and indicate different strategies of social identity construction for each group. An in-group perspective challenges an image of a common identity and demonstrates its fictive nature.
Keywords: national conflict; multicultural state; ethnic minority; Lithuania; Latvia